Melatonin ameliorates serobiochemical alterations and restores the cardio-nephro diabetic vascular and cellular alterations in streptozotocin-induced diabetic rats - Alsharif, Khalaf F.; Elmahallawy, Ehab Kotb; Alblihd, Mohamed A.; Hamad, Asmaa A.; Nasreldin, Nani; Alsanie, Walaa; Aljoudi, Ahmad Majed; Oyouni, Atif Abdulwahab A.; Al-Amer, Osama M.; Albarakati, Alaa Jameel A.; Lokman, Maha S.; Albrakati, Ashraf; et al. (Frontiers in Veterinary Science, 2023)
Melatonin possess a wide range of pharmacological activities, including anti-diabetic properties. Diabetes mellitus (DM) induces several physio-pathological changes in body organs which could be observed lately after systemic failure. In the current study, we targeted to investigate the serobiochemical changes and the histopathological picture in diabetic heart and kidney early before chronic complications, and highlight the association between hyperglycemia, glomerular alterations, and cardiovascular changes. In addition, the role of melatonin in the treatment of cardio-nephro diabetic vascular and cellular adverse changes in streptozotocin-induced diabetic rats was also investigated. A total of forty mature Wister albino rats were distributed into five groups; (1): control untreated, (2): diabetic mellitus untreated (DM), that was induced by injection of Streptozotocin (STZ). (3): Control melatonin treated (MLT), (4): melatonin-treated diabetic (DM+MLT), melatonin was injected (10 mg/kg/day, i.p.) for four weeks, and (5): insulin-treated diabetic (DM+ INS) . The serum biochemical analysis of diabetic STZ rats indicated a significant (P<0.05) increase in the concentrations of blood glucose, total oxidative capacity (TOS), CK-MB, Endothelin-1, myoglobin, H-FABP, ALT, AST, urea and creatinine as compared to control rats. In contrast, there was a significant (P<0.05) decrease in serum concentration of insulin, total antioxidative capacity (TAC), total nitric oxide (TNO) total protein level in DM rats verusus the control. Treatment with melatonin significantly restored all those serobiochemical changes observed in the DM group. A nearby significant improvement in serobiochemical parameters was noticed in both (DM+ MLT) and (DM + INS) groups as compared with (DM) rats. . The histological examination of DM group revealed a disorder of myofibres, cardiomyocyte nuclei, and an increase in connective tissue deposits in between cardiac tissues.Severe congestion and dilation of blood capillaries between cardiac muscle fibers, were also observed. The nephropathy changes in DM rats revealed various deteriorations in glomeruli, and renal tubular cells of the same group. In addition, vascular alterations in the arcuate artery at the corticomedullary junction, and interstitial congestion. Interestingly, melatonin administration repaired all these histopathological alterations near to-control levels. The study concluded that melatonin could be effective therapeutic molecule for restoring serobiochemical, and tissue histopathological alterations during diabetes mellitus.